General education, vocational education, and labor-market outcomes over the life-cycle - Hanushek, Eric A. [Verfasser]; Wössmann, Ludger [Verfasser]; Zhang, Lei [Verfasser] (My University, 2011)
"Policy debates about the balance of vocational and general education programs focus on the school-to-work transition. But with rapid technological change, gains in youth employment from vocational education may be offset by less adaptability and thus diminished employment later in life. To test our main hypothesis that any relative labor-market advantage of vocational education decreases with age, we employ a difference-in-differences approach that compares employment rates across different ages for people with general and vocational education. Using micro data for 18 countries from the International Adult Literacy Survey, we find strong support for the existence of such a trade-off, which is most pronounced in countries emphasizing apprenticeship programs. Results are robust to accounting for ability patterns and to propensity-score matching." (IAB; BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; P 1.8 Ältere; G 1.3.3.1 Qualifikationsverwertung; Betriebliche Berufsausbildung; Arbeitsmarktchance; Älterer Arbeitnehmer; Erwerbsbeteiligung; Technischer Wandel; Qualifikationsverwertung; Allgemeinbildung; Internationaler Vergleich